Study on The Financial Health of State-Owned Construction Companies Based on The Decree of The Minister of State-Owned Enterprises Kep-100/MBU/2002 for The Period 2014-2024 - Risyad Allenby; Raden Aswin Rahadi (Integrasi Sains Media, 2025)
This study assesses the financial stability of four Indonesian state-owned construction firms—PT Adhi Karya (ADHI), PT Pembangunan Perumahan (PTPP), PT Wijaya Karya (WIKA), and PT Waskita Karya (WSKT)—during President Joko Widodo's tenure from 2014 to 2024. The analysis utilizes a dual-method approach by combining the Ministry of State-Owned Enterprises Decree No. KEP-100/MBU/2002 with the Altman Z-Score (2006) model. This combination provides an evaluation based on regulatory compliance and a predictive analysis of future financial difficulties. This study examines solvency, liquidity, profitability, and activity ratios utilizing longitudinal financial data from audited corporate reports. The results indicate that all four organizations underwent a substantial deterioration in financial stability, especially during the 2020–2024 timeframe, attributed to heightened project demands, inadequate asset use, and the economic repercussions of the COVID-19 pandemic. WSKT exhibited the most pronounced drop, characterized by ongoing financial distress indicators as evidenced by Z-Score data. Conversely, ADHI, PTPP, and WIKA exhibited comparatively superior albeit volatile performance. This study emphasizes the significant financial obstacles encountered by state-owned construction businesses in reconciling development objectives with fiscal sustainability. The findings highlight the necessity for enhanced receivables management, debt reorganization, and strategic supervision to prevent enduring financial instability. The results will assist policymakers, regulators, and investors in evaluating the profitability of state-owned enterprises and formulating future infrastructure financing strategies in Indonesia.